Life through the ages II : twenty-first century visions of prehistory - Witton, Mark P., 1984- (Life of the past., 2020)
"What was life like on our planet long before the early humans emerged? Paleontologist Dr. Mark P. Witton draws on the latest twenty-first century discoveries to re-create the appearances and lifestyles of extinct, fascinating species, the environments they inhabited, and the challenges they faced living on an ever-changing planet. A worthy successor to Charles Knight's beloved 1946 classic, Life through the Ages II takes us on an unforgettable journey through the evolution of life on Earth. Dozens of gorgeous color illustrations and meticulously researched, accompanying commentary showcase the succession of lost worlds, defining events, and ancient creatures that have appeared since the earth was formed, creating an indispensable guide to explore what came before us"--